We are fighting the world : a history of the Marashea gangs in South Africa, 1947-1999 - Kynoch, Gary (New African histories series., 2005)
Since the late 1940s, a violent African criminal society known as the Marashea has operated in and around South Africa's gold mining areas. With thousands of members involved in drug smuggling, extortion, and kidnapping, the Marashea was more influential in the day-to-day lives of many black South Africans under apartheid than were agents of the state. These gangs remain active in South Africa. In We Are Fighting the World: A History of the Marashea Gangs in South Africa, 1947-1999, Gary Kynoch points to the combination of coercive force and administrative weakness that characterized the apa.